Relationship quality and e-loyalty towards online travel agency (OTA): social exchange theory perspective - Hamid Rizal,; Hanudin Amin,; Lada Suddin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Drawing from the social exchange theory, the study extends the merits model of ICTR and examine the correlation of communication, transaction, and relational on relationship quality and e-loyalty towards the online travel agency (OTA). The data for the present study were collected from 190 tourists in Sabah, Malaysia. For our data purification and paths analysis, we employed structural equation modeling using PLS-SEM. The initial analysis of the current framework produces strong nomological validity. The path-coefficient analysis indicates that all dimensions of communication, transaction and relational have strong correlations as reliable antecedents for both trust and satisfaction. Correspondingly, the findings indicate that both of our latent constructs of relationship quality positively influence consumers’ sense of e-loyalty towards OTA. The bootstrapping analysis also offers credence on the relationship quality of trust and satisfaction as a significant mediator for e-loyalty. Limitations and recommendations for future research are also discussed and noted.